A Feminist Critical Discourse Analysis of the Tropes of (Sexually) Objectified or/and Oppressed Men in Selected Contemporary African Prose Works - Ayodele Adebayo Allagbé; Yacoubou Alou; Ibrahim Sanusi Chinade (Borong Newinera Publisher, 2021)
This paper examines the tropes of (sexually) objectified or/and oppressed men in selected contemporary African prose works. Drawing on Feminist Critical Discourse Analysis (henceforth, FCDA) for theoretical underpinnings, Systemic Functional Linguistics (henceforth, SFL) for grammatical tools and the qualitative research method, this study seeks to analyze how contemporary feminist writers like Amma Darko, Daniel Mengara, and Lola Shoneyin employ language in their fictional texts The Housemaid (1998), Mema (2003) and The Secret Lives of Baba Segi’s Wives (2015) respectively to represent the phenomenon of (sexually) objectified or/and oppressed male characters. This article cogently argues that the tropes of (sexually) objectified or/and oppressed men, as enacted in the aforementioned prose works, encode a form of gendered experience which irrefutably has a given recondite function or meaning which only a critical linguistic analysis of the writers’ language can uncover. The findings reveal that the three authors intentionally use language to depict their male personae as (sexually) objectified or/and oppressed individuals with a view to challenging the established social order in social life and establishing a certain balance in the representation of gender or/and power relations in African literature.